Perilaku Berbagi Pengetahuan dan Budaya Tim pada Kinerja Inovasi Pelayanan - Nadia Irhamna (UIN Raden Mas Said Surakarta, 2018)
ABSTRACT This study aims to find out the direct influence of knowledge sharing behaviorand the team culture on the service innovation performance. This research uses three variables that are knowledge sharing behavior as an independent variable, team culture as a intervening variable and service innovation performance as a dependent variable. The research uses primary data that is processed using SPSS software. Population in this research is employees of PT. Pos Indonesia branch offices Surakarta, with criteria that have been determined by researchers. The measurements in this questionnaire use a scale of 1 up to 10 intervals and this study used a total of 80 respondents. The result of research indicates that: 1) Knowledge sharing behavior has a significant effect on team culture, 2) Knowledge sharing behavior has a significant effect on service innovation performance, 3) team culture has a significant effect on service innovation performance. Keyword: service innovation performance, knowledge sharing behaviour, team culture.